(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Aldyza N, Barus TA, Mulya MB, Sarong MA. 2022. Coral resilience inside and outside of Pesisir Timur Pulau Weh conservation zone, Sabang City, Indonesia. Biodiversitas 23: 5744-5751. Conservation is one of the efforts to conserve marine life and provide opportunities for an ecosystem to recover. One of the water areas protected by the community is Pulau Weh (Weh Island). In 2010 and 2016, coral reef ecosystems in the waters of Weh Island suffered a lot of damage due to the pressure from nature, i.e., the bleaching phenomenon. As a result, the benthic experienced a vacuum of the substrate. The emptiness of the substrate occurred due to the death of corals and the appearance of a layer of grass algae. Therefore new corals were difficult to recover without a solid and conducive substrate. Hence, this study aims to measure the resilience of corals and benthic conditions inside and outside conservation areas on Weh Island. Benthic data collection used the Point Intercept Transect method while measuring the potential resistance of corals using the resilience index through coral cover, fleshy seaweed, and rubble indicators. Benthic conditions were viewed based on the value of the results of the resilience component with the condition of the coral cover. The result showed that coral reef ecosystems inside and outside the Pesisir Timur Pulau Weh (PTPW; East Coast of Weh Island) conservation area had a high level of resilience (with scores ranging from 3 to 6, out of 6 for benthic condition scores). The benthic inside the conservation area averagely has a good score and it is likely to be in the recovery period from disturbances. While the score for the benthic outside the conservation area is only 3 (out of 6 for benthic condition scores), which indicates that the area is very vulnerable to disturbance even though it has a chance to recover. If there is another bleaching phenomenon in the future, corals that have just tried to recover in this vulnerable area may be damaged again and the coral cover will be decreased.